2005
DOI: 10.1007/s10555-005-1582-z
|View full text |Cite
|
Sign up to set email alerts
|

Rb/E2F: A two-edged sword in the melanocytic system

Abstract: Rb is a tumor suppressor that represses the expression of E2F regulated genes required for cell cycle progression. It is inactivated in melanomas and other cancer cells by phosphorylation catalyzed by persistent cyclin dependent kinase (CDK) activity. CDK activity is sustained in melanoma cells mostly by the elimination of the CDK inhibitor p16INK4A and by high levels of cyclins whose expression is maintained by stimuli emanating from activated cell surface receptors and/or mutated intracellular intermediates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 163 publications
(194 reference statements)
0
43
0
3
Order By: Relevance
“…4 Interestingly, pRb has been reported to bind also other chromatin remodeling factors, such as histone deacetylase, H3 methyl-transferase and members of the chromatin remodeling complex SWI/ SNE, suggesting that pRb together with JARID1B represents a multimolecular scaffold involved in chromatin modification. 67 Performing a series of functional assays, we could confirm the apoptotic and antiproliferative potential of re-expressed full-length RBP2-H1 that was predicted by our genome-wide expression analysis. However, our experiments also suggested that re-establishment of RBP2-H1 may induce apoptosis only in a minor percentage of transfected melanoma cells and that, after this initial spike in apoptosis, remaining cells undergo cell cycle arrest and enhanced proliferation control later on.…”
Section: Discussionmentioning
confidence: 67%
“…4 Interestingly, pRb has been reported to bind also other chromatin remodeling factors, such as histone deacetylase, H3 methyl-transferase and members of the chromatin remodeling complex SWI/ SNE, suggesting that pRb together with JARID1B represents a multimolecular scaffold involved in chromatin modification. 67 Performing a series of functional assays, we could confirm the apoptotic and antiproliferative potential of re-expressed full-length RBP2-H1 that was predicted by our genome-wide expression analysis. However, our experiments also suggested that re-establishment of RBP2-H1 may induce apoptosis only in a minor percentage of transfected melanoma cells and that, after this initial spike in apoptosis, remaining cells undergo cell cycle arrest and enhanced proliferation control later on.…”
Section: Discussionmentioning
confidence: 67%
“…These data demonstrate that Arf down-regulates melanocyte E2F1 levels through a proteasomal-degradation mechanism that could account, at least in part, for its ability to trigger melanocyte growth arrest. Importantly, E2F activity has been associated with senescence in mouse and human melanocytes and has been implicated in human melanoma (24)(25)(26). However, because Arf has many binding partners and other activities (4), additional mechanisms may be involved in Arf-mediated senescence.…”
Section: Resultsmentioning
confidence: 99%
“…10B). Phosphorylation of S780, S795, and S807/811 of RB, known cyclin D:CDK4 and cyclin E:CDK2 targets (Halaban, 2005), is decreased in cells treated with either PD98059 or 219476 (except S780 and S807/811 in OM431 cells), and further reduced in cells with combinatorial treatment (Fig. 10C).…”
Section: Inhibition Of Mek and Cdk4 In Melanoma Cellsmentioning
confidence: 96%
“…It has been well-established that constitutive activation of the ERK signaling induces the expression of cyclin D (Michaloglou et al, 2008;Rotolo et al, 2005), which binds to and activates CDK4 leading to the phosphorylation of RB protein facilitating cell cycle entry (Halaban, 2005). Consistent with an epistatic regulation between ERK pathway and cyclin D:CDK4, amplification of cyclin D1 and CDK4 genes have been identified mainly in melanomas that harbor wild-type NRAS and BRAF (Curtin et al, 2005;Smalley et al, 2008).…”
Section: Inhibition Of Mek and Cdk4 In Melanoma Cellsmentioning
confidence: 96%